Handbook of vanilla science and technology - Havkin-Frenkel, D. (Daphna), 1951-; Belanger, Faith C. (Wiley, 2018)
Vanilla is a flavor and fragrance in foods, cosmetics, pharmaceuticals, and a wealth of other products. Now in its second edition, the Handbook of Vanilla Science and Technology provides a comprehensive and updated review of the science and technology used in these items' production and supply. Featuring contributions from an international range of experts, this revised edition covers a multitude of topics, including agricultural production, global markets, analytical methods, sensory analysis, food and fragrance applications, organic farming and fair trade, botanical diseases, and novel uses.